A cassava clonal evaluation trial based on a new cassava breeding scheme - Ojulong, H; Labuschagne, Maryke T.; Fregene, Martin A.; Herselman, L. (Springer, 2008)
Cassava (Manihot esculenta) breeding at the earlier stages so far has been mainly based on a mass phenotypic recurrent selection, as little data is taken. This has resulted in a long breeding cycle and lack of organised information on the breeding values of parental lines used in the breeding programmes. The International Institute of Tropical Agriculture (CIAT) recently initiated a scheme to try and correct this, by introduction of replication and blocking in the clonal evaluation trial (CET) and collection of data on all genotypes at early stages of breeding. The aim of the study was to evaluate a CET using the new breeding scheme. Replicating and blocking of clones improved the accuracy of the data obtained. High broad-sense heritability values, comparable to those at advanced selection stages, were obtained, as environmental effects were minimised. The highest was for harvest index (HI) (0.80), followed by cassava frogskin disease (CFSD) (0.79), dry matter content (DMC) (0.75) fresh and dry root yields (DRY) (0.73), root weight (RtWt) (0.61), number of commercial roots (0.60) and roots per plant (RtPlt) (0.43). DMC, HI and RtWt were identified as important variables in selection and determination of economic yield at early stages of selection.